Bleb leak revision with Tenon's autograft - Lauren E. Chen; Philina Yee; Andrew K. Smith; Austin Fox; Sameh Mosaed (American Journal of Ophthalmology Case Reports)
This video demonstrates two surgical cases where autologous Tenon grafts are used to shut down leaking trabeculectomies. Variations in this technique with a rotational graft and a hinge graft are explored.